Metaphor and Meaning in David Brooks' The Cold Front and Andrew Lansdown's Windfalls - Perkins, Elizabeth (LiNQ (Literature in North Queensland), 2016)
David Brooks' The Cold Front (Hale and Iremonger, 1983) and Andrew Lansdown's Windfalls (Fremantle Arts Centre Press, 1984), are attractive collections of essentially lyrical and personal poems in which metaphor and image are used to cross the boundaries between subject and object, human and external nature and the inner and the outer world.